Quantifying subjective uncertainty in survey expectations - Krüger, Fabian; Pavlova, Lora (Discussion paper series, 2019)
Several recent surveys ask for a person's subjective probabilities that the in- ation rate falls into various outcome ranges. We provide a new measure of the uncertainty implicit in such probabilities. The measure has several advantages over existing methods: It is trivial to implement, requires no functional form assumptions, and is well-defined for all logically possible probabilities. From a theoretical viewpoint, the measure can be motivated as the entropy function of a strictly proper scoring rule. We demonstrate the measure's good performance in a simulation study based on empirical data from the Survey of Consumer Expectations.
Keywords: Graue Literatur